Studi komunikasi interpersonal dalam pendidikan seks di lingkungan keluarga Bugis-Makassar - Lidayni, Asnur; Suwatno, Suwatno; Gani, Rita (Universitas Garut, 2025)
AbstractThe focus of this study is to examine the pattern of interpersonal communication between parents andstudents in the context of sex education in the Bugis-Makassar cultural environment. The purpose ofthis study is to analyze the role of Bugis-Makassar families in providing sex education to students inMakassar City, including its urgency and family strategies in overcoming various obstacles faced. Thisstudy uses a qualitative approach with descriptive methods, as well as case studies as a researchstrategy applied to Bugis-Makassar students in Makassar City. The data sources in this study consistedof 5 students and 3 parents from the Bugis-Makassar tribe, who were selected using purposivesampling techniques. Data collection techniques include observation, in-depth interviews, anddocumentation. The results of the study indicate that the role of families in providing sex education isstill limited to conveying cultural values, especially the concept of siri' which is highly respected inBugis-Makassar society as a symbol of family honor and dignity. The communication tends to usesimple language and is not scientific. Although in Bugis-Makassar culture there are classicalmanuscripts such as Assikalabineng which contain teachings about sexual relations, this manuscriptis only intended for married individuals. This causes parents to be reluctant to provide open sexeducation information to college-age children. The cultural norm of Siri’ na Pesse emphasizes theimportance of maintaining dignity and self-esteem, so sex education is considered important to form aresponsible understanding of oneself and one’s family. In dealing with communication obstacles,parents tend to use an informal discussion approach in a comfortable atmosphere, by starting theconversation through case studies, such as early marriage and the impact of promiscuity.Keywords: Bugis-Makassar Tribe; family; sex education.AbstrakFokus penelitian ini adalah untuk mengkaji pola komunikasi interpersonal antara orang tua danmahasiswa dalam konteks pendidikan seks di lingkungan budaya suku Bugis-Makassar. Tujuan daripenelitian ini adalah untuk menganalisis peran keluarga Bugis-Makassar dalam memberikanpendidikan seks kepada anak usia mahasiswa di Kota Makassar, termasuk urgensinya serta strategikeluarga dalam mengatasi berbagai kendala yang dihadapi. Penelitian ini menggunakan pendekatankualitatif dengan metode deskriptif, serta studi kasus sebagai strategi penelitian yang diterapkan padamahasiswa suku Bugis-Makassar di Kota Makassar. Sumber data dalam penelitian ini terdiri dari 5mahasiswa dan 3 orang tua yang berasal dari suku Bugis-Makassar, yang dipilih menggunakan teknikpurposive sampling. Teknik pengumpulan data meliputi observasi, wawancara mendalam, dandokumentasi. Hasil penelitian menunjukkan bahwa peran keluarga dalam memberikan pendidikan seksmasih terbatas pada penyampaian nilai-nilai budaya, khususnya konsep siri’ yang dijunjung tinggidalam masyarakat Bugis-Makassar sebagai simbol kehormatan dan martabat keluarga. Komunikasiyang dilakukan cenderung menggunakan bahasa yang sederhana dan tidak bersifat ilmiah. Meskipundalam budaya Bugis-Makassar terdapat naskah klasik seperti Assikalabineng yang memuat ajarantentang relasi seksual, naskah ini hanya diperuntukkan bagi individu yang telah menikah. Hal inimenyebabkan orang tua enggan memberikan informasi pendidikan seks secara terbuka kepada anak-anak usia mahasiswa. Norma budaya Siri’ na Pesse menekankan pentingnya menjaga martabat danharga diri, sehingga pendidikan seks dianggap penting untuk membentuk pemahaman yangbertanggung jawab terhadap diri sendiri dan keluarga. Dalam menghadapi kendala komunikasi, orangtua cenderung menggunakan pendekatan diskusi informal dalam suasana yang nyaman, denganJurnal Komunikasi Universitas Garut: Hasil Pemikiran dan PenelitianE-ISSN: 2580-538X, Volume 11, No. 1, April 2025, hlm. 140-160memulai pembicaraan melalui studi kasus, seperti pernikahan dini dan dampak dari pergaulan bebas.Kata-kata kunci: Keluarga; pendidikan seks; Suku Bugis-Makassar.